2018
DOI: 10.1002/cne.24425
|View full text |Cite
|
Sign up to set email alerts
|

Localization of nectin‐2α at the boundary between the adjacent somata of the clustered cholinergic neurons and its regulatory role in the subcellular localization of the voltage‐gated A‐type K+ channel Kv4.2 in the medial habenula

Abstract: The medial habenula (MHb), implicated in stress, depression, memory, and nicotine withdrawal syndromes, receives septal inputs and sends efferents to the interpeduncular nucleus. We previously showed that the immunoglobulin-like cell adhesion molecules (CAMs) nectin-2α and nectin-2δ are expressed in astrocytes in the brain, but their expression in neurons remains unknown. We showed here by immunofluorescence microscopy that nectin-2α, but not nectin-2δ, was prominently expressed in the cholinergic neurons in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(29 citation statements)
references
References 93 publications
3
11
0
Order By: Relevance
“…The results shown are representative of three independent experiments et al, 2015). We previously showed that nectin-2α localized at the boundary between adjacent somata of clustered cholinergic neurons constitutes nectin-2α spots with which none of l-afadin, s-afadin, cadherins, and their binding proteins is associated (Shiotani et al, 2018). In contrast, the nectin-2α-mediated adhesion apparatus identified here at the contact sites between F I G U R E 1 6 Nectin-2α colocalization with l-afadin, cadherin-8, αN-catenin, and F-actin in the S1 region of the MHb.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The results shown are representative of three independent experiments et al, 2015). We previously showed that nectin-2α localized at the boundary between adjacent somata of clustered cholinergic neurons constitutes nectin-2α spots with which none of l-afadin, s-afadin, cadherins, and their binding proteins is associated (Shiotani et al, 2018). In contrast, the nectin-2α-mediated adhesion apparatus identified here at the contact sites between F I G U R E 1 6 Nectin-2α colocalization with l-afadin, cadherin-8, αN-catenin, and F-actin in the S1 region of the MHb.…”
Section: Discussionmentioning
confidence: 99%
“…We previously showed by immunofluorescence microscopy on the adult MHb using the anti-nectin-2α/δ mAb that two different staining patterns of the immunofluorescence signal for nectin-2α are observed: one is a linear pattern and the other is a punctate pattern (Shiotani et al, 2018). Consistent with these previous observations, the signal for nectin-2α with the linear pattern was observed mainly in the MHbI and the MHbCv of the adult MHb (Figure 2a,b, arrowheads), whereas that with the punctate pattern was observed in the whole regions of the MHb (Figure 2a,b, arrows).…”
Section: Nectin-2α Localization In Synaptic Regions Of the Mhbmentioning
confidence: 99%
See 3 more Smart Citations